Reviving the old sermon of medicine with the placebo effect - Cho,Hyong Jin (2005)
OBJECTIVE: The message of the importance of a caring doctor-patient relationship is now like an old sermon which does not impact anyone's mind or action. Observing the healing practice of the old time physicians, who valued their attitudes and relationship with their patients more than the actual interventions, this paper reviews the literature on their main therapeutic device - the placebo effect - as a novel way of delivering this old sermon of medicine to contemporary doctors. DISCUSSION: There are countless historical and contemporary examples of the impressive placebo effect and although contested by some, it seems real and significant. The classic conditioning theory and the expectation theory explain reasonably well the mechanisms of the placebo effect, especially in conjunction with each other. The underlying biochemical pathway, according to the limited current knowledge, involves endorphins for pain and dopamine for Parkinson's disease. Finally, human factors such as the doctor's positive attitudes and a good doctor-patient relationship seem to be more essential than the placebo itself in eliciting the placebo effect. CONCLUSIONS: Given the body of evidence supporting the existence of significant placebo effect and the importance of the doctor-patient relationship in determining it, the human factors of the medical treatment should be emphasised in order to maximise the placebo effect and consequently the overall therapeutic effect of the healing acts.